A revision and extension of the prevention of escalating adolescent crisis events (PEACE) protocol. (December 2015) - Michael, Kurt; Jameson, John Paul; Sale, Rafaella; Orlando, Carissa; Schorr, Marisa; Brazille, Morgan; Stevens, Anne; Massey, Cameron
Abstract: The disparity between urban and rural suicide rates is increasing. In response to this major public health problem, clinicians and school mental health researchers designed a systematic crisis intervention protocol to be used with adolescents presenting with suicidal or homicidal ideation. The prevention of escalating adolescent crisis events (PEACE) protocol is a comprehensive risk assessment designed for use by licensed clinicians working collaboratively with school personnel. A revised and extended version of the PEACE protocol was employed during 68 crisis events involving 42 high school students in 2013–14. These results and clinical implications of utilizing a systematic protocol to address potential suicidal or violence threats are discussed. Highlights: A revised and extended version of The PEACE protocol was employed in a rural school. The results from the revised PEACE protocol were clinically meaningful. The PEACE protocol is a promising method of intervening with adolescents who present as suicidal in school settings.